Characterization of the public and massive construction of social interest houses developed since 2005 in Lara state. Venezuela (Gaceta Técnica, 2018)
The main objective of this research is the public and massive construction of social interest housing, executed between 2005 and 2015 in the Iribarren and Palavecino municipalities of Lara State, Venezuela, in order to continue the investigation carried out in the years between 1994 and 2005, through the determination of evaluation parameters related to the design and construction characteristics of town planning and housing. It is a field research, not experimental descriptive, the representation shows 355 houses in 5 urbanisms. The relevant results showed a better architectural distribution of the houses than the ones developed in previous years, it showed an 80 % of urban equipment, 20,56% of the houses enclosures problems, 26,42% problems  related to the soil, 16.9% reveals the entry of  rain water and through windows 12.68% presents rain water entry  through the door. Although the percentages of housing failures have been reduced, the percentages of faults in infrastructure services have increased, that is, better homes that lack basic services have been built. Recommending taking advantage of the identified opportunities for improvement.
Keywords: popular housing; characterization of public construction; fault symptomatology